False-Mastic Psylla, Ceropsylla sideroxyli Riley (Insecta: Hemiptera: Psyllidae) - Frank W. Mead (EDIS)
EENY-370, a 3-page illustrated fact sheet by Frank W. Mead, describes this jumping plant louse which causes severe damage to the leaves of the false-mastic tree. Part of the Featured Creatures series, this publication covers the description, host plants, and selected references. Published by the UF Department of Entomology and Nematology, May 2006.